Ecotoxicological effects of pesticides on freshwater snails - Luyo-Martínez, Isbeth Ingrid (2025)
The increasing use of pesticides generates negative effects on biodiversity by exposing freshwater snails, which stand out as the most affected group of gastropods globally. Therefore, the objective of this research is to analyze the ecotoxicological effects of pesticide exposure on freshwater snails, evaluating the impacts on various organs. For this purpose, a search was carried out in databases such as Scopus, Sciencedirect, Web of science and Scielo, in a specific interval of years, 1999-2024. In this context, the articles analyzed focused on the evaluation of different species, especially Lymnaea stagnalis (Linnaeus, 1758), Physella acuta (Draparnaud, 1805), Chilina parchappii (d'Orbigny, 1835) and Planorbarius corneus (Linnaeus, 1758) due to their sensitivity to various pollutants and adaptation to different laboratory conditions, which facilitates their use in controlled research. Likewise, most of the studies reviewed focused on organophosphate, carbamate and pyrethroid pesticides, which cause lethal and sublethal effects such as neurotoxicity, oxidative stress, organ damage and reproductive alterations. In conclusion, ecotoxicological studies on different snail species have provided valuable information on pesticide exposure and effects, highlighting the importance of implementing appropriate conservation and management measures to protect these individuals.